LncRNA ANRIL protects against oxygen and glucose deprivation (OGD)-induced injury in PC-12 cells: potential role in ischaemic stroke - Bin Liu; Wei Cao; Jian Xue (Artificial Cells, Nanomedicine, and Biotechnology)
lncRNA ANRIL was reported to be closely related to ischaemic stroke (IS). In this study, we used oxygen-glucose deprivation (OGD) to stimulate rat adrenal medulla-derived pheochromocytoma cell line PC-12 to construct an in vitro IS cell model and investigated the role of ANRIL and the underlying mechanism. PC-12 cells were stimulated by OGD and/or transfected with pc-ANRIL, si-ANRIL, miR-127 mimic, miR-127 inhibitor, pEX-Mcl-1, sh-Mcl-1 and their negative controls. Cell viability, apoptosis, mRNA and protein expression was detected using CCK-8 assay, flow cytometry assay, qRT-PCR and western blot, respectively. Results showed that OGD-induced PC-12 cell injury and decreased ANRIL expression. ANRIL overexpression significantly reduced OGD-induced PC-12 cell injury evidenced by increasing cell viability and decreasing apoptosis, while ANRIL silence led to the opposite results. Meanwhile, dysregulation of ANRIL altered the expression of apoptotic proteins. Furthermore, ANRIL negatively regulated miR-127 expression. miR-127 overexpression significantly enhanced OGD-induced PC-12 cell injury. In addition, Mcl-1 expression was negatively regulated by miR-127, besides ANRIL up-regulated Mcl-1 expression by down-regulation of miR-127. Mcl-1 overexpression alleviated cell injury and miR-127 silence up-regulated Mcl-1 expression. In conclusion, lncRNA ANRIL alleviated OGD-induced PC-12 cell injury as evidenced. PI3K/AKT pathway might be involved in this regulating progression.